Life Style-Related Diseases of the Digestive System: Endocrine Disruptors Stimulate Lipid Accumulation in Target Cells Related to Metabolic Syndrome - Koichiro Wada; Hirotada Sakamoto; Kenji Nishikawa; Satoru Sakuma; Atsushi Nakajima; Yohko Fujimoto; Yoshinori Kamisaki (Elsevier, 2007)
Many reports indicated that endocrine disruptors (EDs) affect several hormonal functions in various living things. Here, we show the effect of EDs on lipid accumulation in target cells involved in the onset of metabolic syndrome. Treatment with nonylphenol and bisphenol A, typical EDs, stimulated the accumulation of triacylglycerol in differentiated adipocytes from 3T3-L1, preadipocytes, in time- and concentration-dependent manners. Up-regulation of gene expressions involved in lipid metabolism and metabolic syndrome were observed in adipocytes treated with EDs. Similarly, stimulatory effects of EDs were also observed on the human hepatoma cell line HuH-7. These observations indicate that exposure to EDs stimulates the lipid accumulation in target cells involved in the metabolic syndrome and may cause the dysfunction of those cells, resulting in induction of metabolic syndrome. Keywords:: life style-related disease, endocrine disruptor, metabolic syndrome, adipocyte, hepatocyte